Filling the gap in quizizz paper mode research: Its effect on mathematics learning interest at the junior secondary level - Putri Anggun; Rusdi Rusdi; Tasnim Rahmat; Nola Nari; Denilsón Andrés Silgado-Tuñón (Nashir Al-Kutub Indonesia, 2026)
This research is motivated by the low interest in learning mathematics among students, which is thought to be caused by the lack of variety in the use of interactive and interesting technology-based learning media. In addition, the use of learning media that relies on mobile devices often causes distractions, making the learning process less effective. Therefore, this study aims to determine the increase in students’ interest in learning mathematics through the use of interactive learning media Quizizz based on paper mode in grade VII students of MTsN 10 Agam. The type of research used is a pre-experimental study with a one-group pretest-posttest design. The study population was students of grades VII.1 and VII.2, while the research sample was class VII.1 selected using a cluster (class) random sampling technique. The research instrument was a questionnaire on interest in learning mathematics that had been validated and tested for reliability. Data analysis techniques used the t-test and N-Gain test. The results showed that the average score of students’ interest in learning mathematics before treatment was 112.65 and increased to 140.20 after treatment. Based on the results of the t-test analysis, it was found that there was an increase in students’ interest in learning mathematics after using the interactive learning media Quizizz based on paper mode. Furthermore, the N-Gain test result of 0.58 indicates that the increase in student learning interest is in the moderate category. Thus, the use of the paper-based interactive learning media Quizizz can increase students’ interest in learning mathematics.